ANALISIS KINERJA DINAS SOSIAL, PEMUDA DAN OLAHRAGA KOTA SEMARANG DALAM PENANGANAN MASALAH ANAK JALANAN DI KOTA SEMARANG - Sijabat, Rio; Widowati, Nina (Journal of Public Policy and Management Review, 2016)
The research is going to describe and to analyze the performance department social, youths and sports in Semarang and factors that support or detain their performances. Theory that will be used in reasearch are public administration and five dimensions of performance which are productivity, service quality, responsivity, responsibility and accountability with descriptive qualitative study. This research using interview, observation, documentation as method to get information from social services, youth and sports in Semarang and the caretaker of anak emas foundation as the extension hand of the goverment to take care of homeless kids. The result of research is showed that performance of social services, youth and sports in their role to make a better social life for homeless kid is not quite optimal specially in productivity, service quality, and accountability, we see there are some problems in human resources, budgets and lack of information in website also lack of support to another foundation as the extension hand of goverment. However, the performance of department of social, youths and sports had been supported by their ability to discover the street kid’s needs through some programs which are better than the previous year and their obedience to rules and SOP also stick to the principles of administrative as they did their job There are some ideas to counter the problem ,for example, raise the budget, add human resources, more concern about another institution and smoother the services.